2014
DOI: 10.1073/pnas.1311909111
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiplexed interrogation of amplified genes identifies GAB2 as an ovarian cancer oncogene

Abstract: Significance High-grade serous ovarian cancers are characterized by widespread gain and loss of copy number involving large numbers of genes; however, the functional consequences of many of these changes remain unclear. To determine which of the many amplified genes exhibited tumor-promoting behavior, we developed a novel in vivo method to systematically screen potential oncogenes for tumor formation. We identified GAB2, a signaling adaptor protein, as a potent oncogene that is also significantly amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 36 publications
3
54
0
Order By: Relevance
“…GAB2 has previously been implicated as an oncogene in multiple cancer types, including breast cancer (33,34), ovarian cancer (5,35,36), leukemia (37), and melanoma (38). We previously reported that GAB2 is a putative cancer driver gene that is copy number amplified in approximately 15% of HGSC (9, 18), and we extend that analysis here by exploring the correlation of GAB2 expression with improved overall survival and ovarian cancer subtypes.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…GAB2 has previously been implicated as an oncogene in multiple cancer types, including breast cancer (33,34), ovarian cancer (5,35,36), leukemia (37), and melanoma (38). We previously reported that GAB2 is a putative cancer driver gene that is copy number amplified in approximately 15% of HGSC (9, 18), and we extend that analysis here by exploring the correlation of GAB2 expression with improved overall survival and ovarian cancer subtypes.…”
Section: Discussionsupporting
confidence: 61%
“…The gene encodes the scaffolding adaptor GRB2-associated binding protein, a large protein located at the internal cell membrane where it forms a dock for multiple proteins to mediate signals from transmembrane protein kinases (21). GAB2 binds to the p85 regulatory subunit of PI3K to stimulate PI3K signaling, and overexpression of GAB2 has been demonstrated to potentiate ovarian tumorigenesis via the activation of PI3K signaling in an mTOR-dependent manner (36). Other overexpression studies have also linked GAB2 to enhanced epithelial-mesenchymal transition, cell migration, and invasiveness (39) and response to follicle-stimulating hormone (FSH) in ovarian granulosa cells (40), again through the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other work suggests that GAB2 might also be a therapeutic target in AML and some solid tumors. [27][28][29][30][31] In CML patients, leukemic stem cells are relatively resistant to TKI therapy. [47][48][49] Several observations suggest that GAB2 might be required for maintenance of BCR-ABL1…”
Section: Discussionmentioning
confidence: 99%
“…26 Roles for GAB2 in the pathogenesis of several other malignancies have also been reported. [27][28][29][30][31] Here, we use a genetic strategy in mice to define the role of GAB2 in leukemogenesis by BCR-ABL1. Our results indicate an essential role for GAB2 in BCR-ABL1-induced MPN and B-ALL, but demonstrate that distinct GAB2-mediated signaling pathways are required for these 2 hematopoietic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that several genes encoding adaptor proteins are recurrently amplified in lung adenocarcinomas and primary ovarian cancers and essential to proliferation and survival in cancer cells that harbor those amplifications (Brown et al, 2008; Luo et al, 2008, 2015; Kim et al, 2010; Cheung et al, 2011a, 2011b; Wang et al, 2012; Dunn et al, 2014). Overexpression of these genes in immortalized human cell lines promoted anchorage-independent growth and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%